Identification of nutritional composition and antioxidant activities of fruit peels as a potential source of nutraceuticals - Hussain, Tarique; Kalhoro, Dildar Hussain; Yin, Yulong (Frontiers in Nutrition, 2023)
Fruit peels comprise several biologically active compounds, but their nutritional composition and antioxidant potential of different fruit varieties are limited. This study aimed to determine the nutritional composition and antioxidant properties of 12 peels of different fruit varieties such as apples, pomegranates, guavas, strawberries, grapes, and citrus fruits using a ultraviolet-visible (UV-Vis) spectrophotometer, an inductively-coupled plasma atomic emission spectroscopy (ICP-AES), and an amino acid analyzer. The highest values of TPC, TFC, lycopene, ascorbic acid [total carotenoids and total antioxidant capacity (TAC)], reducing sugars, non-reducing sugars, and total soluble proteins were reported in grapes (Black seedless) 54,501.00 ± 0.82 μM/g dry wt., guava (Gola) 198.19 ± 0.46 Rutin equivalent dry wt., strawberry (Candler) 7.23 ± 0.33 mg/g dry wt., citrus (Mausami) 646.25 ± 0.96 ug/g dry wt., apple (Kala kulu-Pak) 14.19 ± 0.38 mg/g dry wt. and 12.28 ± 0.39 μM/g dry wt., strawberry (Candler) 25.13 ± 0.40 mg/g dry wt., pomegranate (Badana) 9.80 ± 0.43 mg/g dry wt., apple (Kala kullu-Irani) 30.08 ± 0.11 mg/g dry wt., and guava (Gola) 638.18 ± 0.24 mg/g dry wt. compared with its opponent peels of fruits, respectively. All 12 peels of the fruit verities had 20 amino acids and presented as dry matter basis%. The highest trend of glutamic acid + glutamine, glycine, and aspartic acid + asparagine was observed in pomegranate (Badana) 1.20 DM basis%, guava (Surhai and Gola) 1.09 and 1.09 DM basis%, and strawberry (Desi/local and Candler) 1.15 and 1.60 DM basis% in response to other fruit peels, respectively. Regarding the mineral profile, the highest values of nitrogen (764.15 ± 0.86 mg/100 g), phosphorus (53.90 ± 0.14 mg/100 g), potassium (3,443.84 ± 0.82 mg/100 g), ferric (1.44 ± 0.00 mg/100 g), magnesium (1.31 ± 0.00 mg/100 g), and manganese (0.21 ± 0.00 mg/100 g) were found in pomegranate (Badana), grapes (Black seedless), apple (Kala kulu-Pak), and pomegranate (Badana), respectively, in context to other fruit peels’ extract. Principal component analysis (PCA) and agglomerative hierarchical clustering (AHC) were analyzed for determining the correlation among different peels of fruits. Significantly, high levels of variation were noticed among different variables of peels of fruit. Fruit variety and its peels have been distinctive variables in selecting genotypes. The dendrogram obtained from cluster analysis was distributed into two groups and consisted of eight varieties in the same group, and four fruit varieties were in second group. Overall, the results conclude that fruit peels have the abundant antioxidants and some minerals, which can effectively be utilized for nutraceuticals as well as for food security.